The #CommunityArchive is Trending: An Analysis of the Affordances and Limitations of Social Media as Community Archives for Collective Memory in the Public Sphere - de Guzman, Nicko (Trinity College (Dublin, Ireland). School of Languages, Literature and Cultural Studies, 2021)
The dissertation examines the community archive’s effectiveness in a social media context in terms of accessibility, transmission, and sustainability among other factors that deal with archival functions and goals. The critical digital humanities approach to this paper is done by taking cultural-humanities concepts (collective memory and archives) and connecting it with a sociological theory (the public sphere) while being contextualized in a digital-technical milieu (social media). The dissertation wants to argue that collective memory is as much a discourse facilitator that informs public opinions in a public sphere as compared to the news. Archives, then, act as a physical entity containing discourse of collective memory just as a newspaper is for news. These concepts are then transposed in social media: Facebook, Twitter, and Instagram as the new public sphere. The emergence of community archives on social media and their goals of inclusion are then critiqued if indeed social media suffices as an interface to include a community archive’s collective memory in the public sphere. This is done through analysing specific social media aspects such as filters and vague terms and by examining how a particular community archive, the Black and Irish, functions in social media. The results show that the affordances of social media as an interface for community archives are countered by the limitations and barriers embedded in the social media system and its business model that impedes archival functions and goals of collective memory inclusion in the public sphere.
Keywords: Digital Humanities and Culture